2016
DOI: 10.1002/ejlt.201600239
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of filter‐based NIR spectroscopy for the routine measurement of olive oil fruit ripening indices

Abstract: The aim of this work was to apply and validate a NIR spectrometer based on a discrete filter system for the rapid measurement of the moisture, oil, sugar, and phenolic compounds contents of olive oil fruits. The batches of olive oil fruits were collected during seven crop seasons from several farms located in Tuscany and then they were crushed into olive paste. The water content was measured gravimetrically, oil content was measured using the Soxhlet method, sugar content was measured enzymatically and phenoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
2
5
1
Order By: Relevance
“…For total phenolic content, FT-MIRs in the region of 3,996 and 758 cm −1 , have been shown to provide rough predictions (RPD = 1.57), while those developed in the NIR region were shown to be unreliable (RPD = 1.26). Contrary to our results, Trapani et al (2016) reported that the NIR spectral region of 12,500 to 4,000 cm −1 provided relatively good prediction statistics ( R 2 = 0.71, RMSEP = 0.08 mg/kg dm) for total phenolic content in olive oil. Model development for the yellowness index gave relatively poor prediction statistics for both FT-NIRs and FT-MIRs ( Table 2 ).…”
Section: Resultscontrasting
confidence: 99%
“…For total phenolic content, FT-MIRs in the region of 3,996 and 758 cm −1 , have been shown to provide rough predictions (RPD = 1.57), while those developed in the NIR region were shown to be unreliable (RPD = 1.26). Contrary to our results, Trapani et al (2016) reported that the NIR spectral region of 12,500 to 4,000 cm −1 provided relatively good prediction statistics ( R 2 = 0.71, RMSEP = 0.08 mg/kg dm) for total phenolic content in olive oil. Model development for the yellowness index gave relatively poor prediction statistics for both FT-NIRs and FT-MIRs ( Table 2 ).…”
Section: Resultscontrasting
confidence: 99%
“…In the considered drupes, moisture content ranged from 39.3 to 87.2%. The obtained results agree with previously published data [ 18 , 35 ], considering that the moisture mean value was 63.3%, while the highest values (>80%) were obtained only in three out of thirteen cultivars, all from Calabria region. Excluding those three cultivars, the maximum value for moisture was 73.7%.…”
Section: Resultssupporting
confidence: 92%
“…Similar model performances in calibration and cross-validation were obtained for 1/TPC for all the spectral acquisition systems (R 2 range, 0.76–0.89), whereas in prediction FT-NIR spectra, gave better results (R 2 pred = 0.77–0.76) than Vis/NIR spectra (R 2 pred = 0.69). FT-NIR models are better than those reported in the literature for a filter-based NIR spectrometer [ 35 ]. The authors attributed the unsatisfactory output of their model (R 2 cal , 0.72; SEP, 13.35 g oleuropein/kg dm ) to the exclusion of 8600–6900 cm −1 range from the spectral bands, which was instead here considered.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…e results in terms of R 2 for the calibration, prediction, and cross validation ranged between 0.930 and 0.998, 0.874 and 0.942, and 0.837 and 0.992, respectively. A recent preliminary study of Trapani et al [109] applied cost-saving NIR based on a discrete filter system for the rapid measurement of total phenolic content and oleuroperin of olive fruits, in addition to the moisture, oil, and sugar. Although PLS models built for the latter ones were satisfactory, the instrument did not prove itself suitable for obtaining predictive models for phenolic compound contents.…”
Section: Phenolic Compounds Tocopherols and Squalenesmentioning
confidence: 99%